(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This article presents a comprehensive analysis of full mouth rehabilitation (FMR) in prosthodontics, emphasizing the restoration of occlusal harmony, esthetics, and functional balance in patients with severely compromised dentition. Full mouth rehabilitation involves a systematic approach that integrates diagnostic evaluation, occlusal analysis, and restorative planning to rebuild the entire dentition for optimal form and function. The paper explores fundamental principles such as vertical dimension of occlusion, centric relation, anterior guidance, and posterior disclusion, all of which are essential to achieving long-term success. It also discusses the esthetic considerations, material selection, and multidisciplinary coordination required to meet both functional and visual demands. The study highlights the role of digital technology, articulators, and advanced restorative materials in improving precision and predictability. Through an evidence-based perspective, the article outlines the clinical protocols, biomechanical principles, and aesthetic guidelines that govern successful full mouth rehabilitation and long-term patient satisfaction. This article provides an in-depth analysis of full mouth rehabilitation (FMR) as a comprehensive approach in prosthodontics, focusing on the restoration of occlusal balance, functional efficiency, and esthetic integration. It highlights how modern diagnostic and digital technologies have transformed treatment planning, allowing clinicians to precisely evaluate vertical dimension, centric relation, and mandibular dynamics. The research explores how biomechanical principles, occlusal design, and material advancements contribute to long-term clinical success. Emphasis is placed on the synchronization between the stomatognathic system components—teeth, temporomandibular joints, and muscles—to achieve equilibrium and durability. Moreover, it discusses esthetic considerations such as facial harmony, tooth proportion, and smile design, which are integral to achieving both function and patient satisfaction. Through evidence-based analysis, the study demonstrates that full mouth rehabilitation requires a holistic understanding of physiology, biomechanics, and artistry to reestablish a stable, functional, and visually pleasing oral environment.